Distal Spinal Muscular Atrophy: An Overlooked Etiology of Weaning Failure in Children with Respiratory Insufficiency - Habibi Zoham, Mojdeh; Eghbalkhah, Asgar; Kamrani, Kamyar; Khosroshahi, Nahid; Yousefimanesh, Hossein; Eskandarizadeh, Zahra (Journal of Pediatric Intensive Care, 2018)
Spinal muscular atrophy with respiratory distress type 1 (SMARD1) is a rare autosomal recessive neuromuscular disorder that involves the anterior horn motor neurons. It is a disease with a poor prognosis presenting with progressive distal motor weakness and respiratory insufficiency from diaphragmatic paralysis followed by distal muscle weakness before 6 months of age. With the intent to spread the awareness of this rare and life-threatening disease, we report a 2.5-month-old female infant with a subsequent diagnosis of SMARD1, who was admitted in our pediatric intensive care unit with chief complaint of progressive respiratory distress and poor feeding.
Keywords: respiratory insufficiency; spinal muscular atrophy; diaphragmatic paralysis